Piperine improves the sensitivity of osteosarcoma cells to doxorubicin by inducing apoptosis and inhibiting the PI3K/AKT/GSK-3β pathway - Yubin Qi; Lin Yao; Jianke Liu; Wen Wang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Osteosarcoma is a primary bone malignancy associated with the highest incidence rate. Chemotherapy for osteosarcoma has not substantially changed, and survival of patients with metastatic tumours has reached a plateau. Doxorubicin (DOX) is a broad-spectrum anti-osteosarcoma drug; however, its application is limited due to its high cardiotoxicity. Piperine (PIP) has been verified to drive certain cancer cell death and increases chemosensitivity of DOX. However, the effects of PIP in promoting the chemosensitivity of osteosarcoma to DOX have not been studied. Methods We examined the combined effect of PIP and DOX on U2OS and 143B osteosarcoma cells. CCK-8 assays, scratch assays, flow cytometry analysis, and western blotting were performed. Furthermore, the effect of PIP combined with DOX on osteosarcoma tumours was observed in vivo using nude mice. Results PIP can increase the chemosensitivity of U2OS and 143B cells to DOX. Both in vitro and in vivo results showed the dramatic inhibition of cell proliferation and tumour growth by the combined therapy group compared to monotherapy groups. Apoptosis analysis revealed that PIP augments DOX-induced cell apoptosis by upregulating BAX and P53 expression, as well as reducing Bcl-2 expression. Furthermore, PIP also attenuated the initiation of the PI3K/AKT/GSK-3β signaling pathway in osteosarcoma cells by altering the expression levels of P-AKT, P-PI3K and P-GSK3β. Conclusions This study revealed for the first time that PIP can potentiate the sensitivity and cytotoxicity of DOX during osteosarcoma therapy in vitro and in vivo, which probably achieved by inhibiting the PI3K/AKT/GSK-3β signalling pathway.